Tourist Preferences at Hotel and Resort Based on Review Data - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study investigates the relationship between cultural dynamics and tourist preferences in hotel and resort settings through comprehensive review data analysis across multiple countries of origin. Using thematic analysis methodology implemented through Atlas.Ti software, the research examines patterns in accommodation preferences, service expectations, and satisfaction determinants. The findings reveal significant variations in guest preferences across different cultural backgrounds, with statistical analysis showing distinctive patterns in visitor demographics. Notably, couples constitute the highest proportion of visitors across multiple destinations, with exceptionally high concentrations in Hong Kong (92%), Malta (90%), and Argentina (62%). Cultural influences manifest through specific preferences in room configurations, dining experiences, and recreational offerings, where Asian tourists emphasize personalized service interactions and traditional elements. At the same time, European visitors prioritize authentic local experiences within luxury accommodation frameworks. The study identifies four key dimensions of managerial adaptation: cultural sensitivity, customization, staff training, and service modifications. These findings contribute to advancing understanding of cultural influences in hospitality contexts while providing practical guidelines for enhancing guest experiences in international hotel operations. The research concludes that effective cultural adaptation strategies enhance guest satisfaction and create sustainable competitive advantages in increasingly globalized hospitality markets.